Cellular Aluminium Foam Metal Production with Space Holder Particles - Ozer, Goekhan; Guler, Kerem Altug; Taslicukur, Zeynep (CARL HANSER VERLAG, 2010)
Metal foams are a new class of materials with low densities and novel physical, mechanical, thermal, electrical, and acoustic properties. Aluminum foams especially show potential for use in lightweight structures, for energy absorption, and for thermal management. Open cell aluminum foams with tailored porous morphology were synthesized by a space-holder method. In these foams, the pore shape is predominantly controlled by the initial shape of the space-holder particles that are used to produce the preform. In this study, resin bonded sand and gypsum bonded ceramic space holder particles are used in the open cell foam production. This paper describes the space-holder method for manufacturing open cell aluminum foams and characterizes the density as well as the compressive property of the foams.
Keywords: Materials Science